2019
DOI: 10.1093/pubmed/fdz014
|View full text |Cite
|
Sign up to set email alerts
|

Dentition status among an ethnically diverse older urban Malaysian population

Abstract: Background Poor oral health affects not only dietary choices but overall well-being. This study explores the influence of lifestyle, socio-demographics and utilization of dental services on the dentition status of an older urban Malaysian population. Methods A total of 1210 participants 60 years and above, representing the three main ethnic groups were recruited from a larger cohort study. Weighted factors valued for comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Malays and Chinese also had significantly higher DMFT scores compared with Indians. A previous study reported similar results where Malays and Chinese had more filled teeth compared with Indians [ 37 ]. This may be a reflection of how different ethnicities perceive the importance of oral health care and utilize dental services in Malaysia [ 37 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Malays and Chinese also had significantly higher DMFT scores compared with Indians. A previous study reported similar results where Malays and Chinese had more filled teeth compared with Indians [ 37 ]. This may be a reflection of how different ethnicities perceive the importance of oral health care and utilize dental services in Malaysia [ 37 ].…”
Section: Discussionmentioning
confidence: 53%
“…A previous study reported similar results where Malays and Chinese had more filled teeth compared with Indians [ 37 ]. This may be a reflection of how different ethnicities perceive the importance of oral health care and utilize dental services in Malaysia [ 37 ]. Hence, the null hypothesis that there are no differences in dental health between ethnicities was rejected.…”
Section: Discussionmentioning
confidence: 53%
“…Ageism is often expressed through cultural values and social beliefs. These ageist stereotypes may intersect with other discriminatory attitudes which might be culturally driven 29–31 . Thus, cross‐cultural adaptation is crucial when one uses an instrument in a different linguistic and cultural background to minimize the risk of bias 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (2022) and some other studies showed that the non-white elderly used oral and dental services less often [ 62 – 65 ]. Also, Amanat et al (2020) suggested that tooth decay and tooth loss in the Chinese elderly was less frequent than in the Malay elderly [ 66 ]. Financial problems, racial discrimination, differences in oral and dental health literacy, perception of needs, barriers to access, and dissatisfaction with dental care among elderly people of different races could be the reasons for it [ 63 , 67 ].…”
Section: Discussionmentioning
confidence: 99%